PLEX.I: a tool to discover features in multiplex networks that reflect clinical variation - Yousefi, Behnam; Firoozbakht, Farzaneh; Melograna, Federico; Schwikowski, Benno; Van Steen, Kristel (Frontiers in Genetics, 2023)
Molecular profiling technologies, such as RNA sequencing, offer new opportunities to better discover and understand the molecular networks involved in complex biological processes. Clinically important variations of diseases, or responses to treatment, are often reflected, or even caused, by the dysregulation of molecular interaction networks specific to particular network regions. In this work, we propose the R package PLEX.I, that allows quantifying and testing variation in the direct neighborhood of a given node between networks corresponding to different conditions or states. We illustrate PLEX.I in two applications in which we discover variation that is associated with different responses to tamoxifen treatment and to sex-specific responses to bacterial stimuli. In the first case, PLEX.I analysis identifies two known pathways [i] that have already been implicated in the same context as the tamoxifen mechanism of action, and [ii] that would have not have been identified using classical differential gene expression analysis. Availability and implementation: PLEX.I is freely available under a GPL-3 license on CRAN (https://cran.r-project.org/web/packages/PLEXI/index.html) and on GitHub (https://github.com/behnam-yousefi/PLEXI). Documentation, examples and usage instructions are also provided in the GitHub repository.